Serum‐mediated Haemonchus contortus larval aggregation differs by larval stage and is enhanced by complement. (March 2017) - Garza, J. J.; Greiner, S. P.; Bowdridge, S. A.
Summary: The objectives of this study were to measure Haemonchus contortus larval aggregation by complement/antibody complexes, determine effect of breed resistance and infection status and determine the effect of larval maturation on larval aggregation in vitro . Larval binding assays were performed on H. contortus L3, exsheathed L3 and L4 incubated with serum from either parasite naïve or H. contortus primed St. Croix (resistant) and Suffolk (susceptible) lambs. No differences in L3 aggregation were observed between serum from either breed or infection status. Exsheathed L3 (60%) and L4 (42%) aggregation by primed Suffolk serum was significantly reduced compared with L3 (80%, P <.001). Removal of either complement or antibody effectively eliminated L3 aggregation ( P <.001). Combination of antibody‐depleted and complement‐inactivated serum restored L3 aggregation to levels consistent with unprocessed serum, supporting a role for antibody and complement in aggregation ( P <.001). Use of fluorescence‐labelled anti‐sheep IgG antibody allowed documentation of IgG bound to serum complexes within L3 masses and was present only in larvae incubated with normal serum, and complement‐ and antibody‐depleted serum combination. These data indicate that complement/antibody complexes inhibit larval motility through larval aggregation which may be critical in early larval clearance of H. contortus .